Answer:
[tex]\displaystyle f'(x) = 2x + 1[/tex]
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Distributive Property
Algebra I
- Terms/Coefficients
- Expanding
- Factoring
- Functions
- Function Notation
Calculus
Limits
Limit Rule [Variable Direct Substitution]: [tex]\displaystyle \lim_{x \to c} x = c[/tex]
Derivatives
- [tex]\displaystyle f'(x) = \lim_{h \to 0} \frac{f(x + h) - f(x)}{h}[/tex]
Derivative Notation
Step-by-step explanation:
Step 1: Define
Identify
f(x) = x² + x - 2
Step 2: Differentiate
- Substitute in function [Limit Process]: [tex]\displaystyle f'(x) = \lim_{h \to 0} \frac{[(x + h)^2 + (x + h) - 2] - (x^2 + x - 2)}{h}[/tex]
- [Brackets] Expand: [tex]\displaystyle f'(x) = \lim_{h \to 0} \frac{[x^2 + 2hx + h^2 + x + h - 2] - (x^2 + x - 2)}{h}[/tex]
- [Distributive Property] Distribute negative: [tex]\displaystyle f'(x) = \lim_{h \to 0} \frac{x^2 + 2hx + h^2 + x + h - 2 - x^2 - x + 2}{h}[/tex]
- Combine like terms: [tex]\displaystyle f'(x) = \lim_{h \to 0} \frac{2hx + h^2 + h}{h}[/tex]
- Factor: [tex]\displaystyle f'(x) = \lim_{h \to 0} \frac{h(2x + h + 1)}{h}[/tex]
- Simplify: [tex]\displaystyle f'(x) = \lim_{h \to 0} 2x + h + 1[/tex]
- Evaluate limit [Limit Rule - Variable Direct Substitution]: [tex]\displaystyle f'(x) = 2x + 0 + 1[/tex]
- Simplify: [tex]\displaystyle f'(x) = 2x + 1[/tex]
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Derivatives
Book: College Calculus 10e